The Effectiveness of Family Instruction Program in schools of Tehran Based on Context, Input, Process, and Product Model - Alamin, Zohre; Karimzadeh, Samad; Bakhtiyari, Abolfazl (International Journal of Education and Cognitive Sciences, 2022)
Introduction: Family instruction is one of the most fundamental and safest ways for developing families. This study was based on the Context, Input, Process, and Product (CIPP) evaluation model.  The main objective was to investigate the effectiveness of family instruction programs in the schools of Tehran, Iran in the academic years of 2012-2013.  Materials and methods: The population size was 6000. The sample size was 360 parents who were selected through convenience sampling. Data were collected through two researcher made instruments (one instrument for parents and one for teachers). Data were analyzed through independent t-test. Results: The results of the study showed that family instruction program (based on CIPP model) is very effective. It increases the parents’ knowledge. Moreover, this program increases parents’ knowledge about spiritual training methods and recognizing the physical needs of the adolescents. Conclusion: It can be concluded that such instruction programs also promotes the parents information and knowledge about the adolescents growth and development for better understanding  of psychological and emotional needs, promoting the relationships between family and parents training methods, and improving the relationships between parents and teachers.